The frequence of human papillomavirus (HPV) DNA on cervical cancer patients from several hospitals in Yogyakarta by PCR test. - Titik Nuryastuti, Titik Nuryastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background : Cancer of the uterine cervix (cervical cancer) is one of the most common malignant neoplasm in women in developing countries and remains a major public health problem worldwide. Several studies have proved the role of HPV as an agent STD (sexually transmitted disease), in the pathogenesis of Cervical cancer, beside the other risk factors.Objective : The aim of this study was to know the frequence of HPV infection in Yogyakarta.Material and Methods : 44 samples of Cervical cancer biopsies were collected from Sardjito General Hospital, Bethesda Hospital and private doctors, and stored frozen. DNA isolated from the biopsies of cervical cancer was amplified by PCR using consensus primer (CP I and CP IIG) from El ORF (188 bp) of HPV.Result : HPV DNA was detected in 84.1 % of the samples. In CIN I, 20 % samples were infected with HPV, 100 % in Ca epidermoid, 66.4 % in adeno Ca and 0 % in Ca adenosquamosaConclusion : The frequency of HPV in cervical Ca biopsies of certain histopathological status in Yogyakarta by PCR method was proved to be very high.Key words : HPV infection - cervical Ca - biopsy - PCR